Can We Teach Non-Cognitive Outcomes? A Quasi-Experimental Study of Philosophy for Children - Nadia Siddiqui; Stephen Gorard; Beng Huat See (MDPI AG, 2022)
Non-cognitive learning taking place at school helps form dispositions that can be as important as cognitive outcomes in terms of lifelong relevance. There are diverse interventions and school-based programmes targeting non-cognitive skills, but the evidence of their impact is, so far, unclear. To help increase the evidence bases, we conducted a quasi-experimental study involving 486 pupils in 18 primary schools in North Yorkshire, England, wherein 11 schools participated in Philosophy for Children (P4C), and 7 schools formed a control group that received lessons as normal. At the baseline, the two groups were not equivalent, which means the results need to be treated with appropriate caution. Pupils who received the P4C intervention scored higher on all attitudes and views than they had at the start and improved more than comparator pupils in terms of empathy and fairness. However, they were behind the comparator group in terms of teamwork and democracy, and there was little difference in terms of their self-reported ability to communicate with others. In general, the P4C approach was found to be feasible, and was generally liked by teachers and pupils. Teachers reported improvements in pupil conduct and confidence in P4C sessions and in other learning activities. The indications are that non-cognitive skills are potentially malleable and might be improved through a dialogic approach, such as P4C.